Study of the colloidal stability and optical properties of sunscreen creams - Saito, Gustavo Pereira; Bizari, Mariana; Cebim, Marco Aurélio; Correa, Marcos Antonio; Jafelicci Junior, Miguel; Davolos, Marian Rosaly (Eclética Química, 2019)
Sunscreen formulations containing inorganic/organic filters or mixture of them were synthesized by oil/water dispersion. The viscosity measurements show that sunscreen formulations are time-dependent non-newtonian fluids. In the CIELab color diagram, the white and/or beige colors presented by formulations do not compromise the aesthetics of the cosmetic product. UV-VIS absorption spectra show that sunscreen creams have high UV shielding ability, mainly the formulations containing inorganic and organic filters mixtures, which provide in vitro SPF and critical wavelength values recommended for UV protection.